Regret after Gender-affirmation Surgery: A Systematic Review and Meta-analysis of Prevalence. Issue 3 (March 2021) - Bustos, Valeria P.; Bustos, Samyd S.; Mascaro, Andres; Del Corral, Gabriel; Forte, Antonio J.; Ciudad, Pedro; Kim, Esther A.; Langstein, Howard N.; Manrique, Oscar J.
Abstract : Background: There is an unknown percentage of transgender and gender non-confirming individuals who undergo gender-affirmation surgeries (GAS) that experiences regret. Regret could lead to physical and mental morbidity and questions the appropriateness of these procedures in selected patients. The aim of this study was to evaluate the prevalence of regret in transgender individuals who underwent GAS and evaluate associated factors. Methods: A systematic review of several databases was conducted. Random-effects meta-analysis, meta-regression, and subgroup and sensitivity analyses were performed. Results: A total of 27 studies, pooling 7928 transgender patients who underwent any type of GAS, were included. The pooled prevalence of regret after GAS was 1% (95% CI <1%–2%). Overall, 33% underwent transmasculine procedures and 67% transfemenine procedures. The prevalence of regret among patients undergoing transmasculine and transfemenine surgeries was <1% (IC <1%–<1%) and 1% (CI <1%–2%), respectively. A total of 77 patients regretted having had GAS. Twenty-eight had minor and 34 had major regret based on Pfäfflin's regret classification. The majority had clear regret based on Kuiper and Cohen-Kettenis classification. Conclusions: Based on this review, there is an extremely low prevalence of regret in transgender patients after GAS. We believe this study corroborates the improvements made in regard to selection criteria for GAS. However, there is high subjectivity in the assessment of regret and lack of standardized questionnaires, which highlight the importance of developing validated questionnaires in this population. Abstract : Supplemental Digital Content is available in the text.